Research on Characterization and Processing of Table Olives - Gandul-Rojas, Beatriz; Gallardo-Guerrero, Lourdes (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Written by experts in the field of table olives, this book is a source of recent research advances on the characterization and processing of table olives. Research papers are provided relating to the characterization of their composition of volatiles and the sensory profile; mineral composition and bioavailability; changes in bioactive components (chlorophylls) by processing; and new strategies to reduce sodium and additives for stabilizing the organoleptic properties and avoiding defects in table olives. Other research papers are included in relation to microbiological and chemical changes in table olives during spontaneous or controlled fermentation employing different cultivars, and the optimized use of starter cultures for the improvement of the different fermentative processes. In addition, this book includes an overview of the main technologies used for olive fermentation, including the role of lactic acid bacteria and yeasts characterizing this process, and of the processing and storage effects on the nutritional and sensory properties of table olives.